Renoprotective potentials of small molecule natural products targeting mitochondrial dysfunction - Rahman, Md. Ataur; Akter, Sumaya; Dorotea, Debra; Mazumder, Arpita; Uddin, Md. Naim; Hannan, Md. Abdul; Hossen, Muhammad Jahangir; Ahmed, Md. Selim; Kim, Woojin; Kim, Bonglee; Uddin, Md Jamal (Frontiers in Pharmacology, 2022)
Kidney diseases, including acute kidney injury (AKI) and chronic kidney disease (CKD), have become critical clinical, socioeconomic, and public health concerns worldwide. The kidney requires a lot of energy, and mitochondria act as the central organelle for the proper functioning of the kidney. Mitochondrial dysfunction has been associated with the pathogenesis of AKI and CKD. Natural products and their structural analogs have been sought as an alternative therapeutic strategy despite the challenges in drug discovery. Many studies have shown that small-molecule natural products can improve renal function and ameliorate kidney disease progression. This review summarizes the nephroprotective effects of small-molecule natural products, such as berberine, betulinic acid, celastrol, curcumin, salidroside, polydatin, and resveratrol. Treatment with small-molecule natural products was shown to attenuate renal oxidative stress and mitochondrial DNA (mtDNA) damage and restore mitochondrial biogenesis and dynamics in the kidneys against various injury stimuli. Therefore, small-molecule natural products should be recognized as multi-target therapeutics and promising drugs to prevent kidney diseases, particularly those with mitochondrial dysfunction.